Single Dose IV Peramivir Treatment in Pediatric Influenza: Lack of Development of Influenza Virus Variants with Reduced Susceptibility to Peramivir. (4th October 2017) - Hamelin, Marie-Ève; Abed, Yacine; Carbonneau, Julie; Jeeninga, Rienk; Smits, Saskia; Kulenovic, Smail; Borroto-Esoda, Katyna; Taylor, Ray; Collis, Phil; Boivin, Guy
Abstract: Background: Peramivir (PVR) is a potent neuraminidase inhibitor (NAI) with in vitro activity against all influenza virus subtypes. Previous studies demonstrated the efficacy and safety of peramivir as a single dose intravenous (IV) treatment for acute uncomplicated influenza in adults. Methods: A phase 3 study compared age-appropriate single dose IV PVR to 5 days of oral oseltamivir (OSE) (4:1 randomization, stratified by age) in pediatric subjects age 0–17 years within 48 hours of acute uncomplicated influenza symptom onset. Influenza infection and subtype was confirmed by PCR. In vitro susceptibility of cultured virus to PVR, OSE and zanamivir (ZVR) from paired baseline/ post-treatment nasopharyngeal (NP) swabs was performed with a MUNANA assay. Sequence analysis of NA and hemagglutinin (HA) genes was performed from uncultured virus. Results: 122 subjects were enrolled up to a cutoff date of March 31, 2017 (<2 yrs, n = 7; 2-<7yrs, n = 37; 7-<13 yrs, n = 48; 13–17 yrs, n = 30). Data is shown on 108 subjects randomized prior to the 2016–17 season, of which 101 (94%) received study drug. Full data will be reported. Influenza was confirmed in 75 (74%) subjects who received study drug: A/H1N1, n = 31 (41%); B, n = 27 (36%); A/H3N2, n = 15 (20%); A/indeterminate and A/H1N1/ B co-infected, 1 each. Baseline IC50 s for each subtype are summarized: Two treatment-emergent substitutions were detected in NA or HA genes of PVR-treated subjects: a NA S67A (reversion to wild type) in an influenza B virus and a HA V496V/F mixture in an A/H1N1 virus. Neither substitution was associated with a resistant phenotype. Among PVR treated subjects, no changes were observed in the last positive post-baseline sample PVR median IC50 compared with baseline and no individual subject treated with PVR had an IC50 fold-change from baseline greater than 1.63. Conclusion: Peramivir had the greatest potency of 3 NAIs tested for all baseline virus subtypes in the order: PVR < ZVR < OSE. Treatment with a single dose of IV PVR was not associated with development of resistance to the drug in this pediatric population. Disclosures: M. È. Hamelin, BioCryst Pharmaceuticals: Collaborator, Research support; Y. Abed, BioCryst Pharmaceuticals: Collaborator, Research support; J. Carbonneau, BioCryst Pharmaceuticals: Collaborator, Research support; R. Jeeninga, BioCryst Pharmaceuticals: Collaborator, Research support; S. Smits, BioCryst Pharmaceuticals: Collaborator, Research support; S. Kulenovic, BioCryst Pharmaceuticals: Collaborator, Research support; K. Borroto-Esoda, BioCryst Pharmaceuticals: Consultant, Consulting fee; R. Taylor, BioCryst Pharmaceuticals: Employee, Salary; P. Collis, BioCryst Pharmaceuticals: Employee, Salary; G. Boivin, BioCryst Pharmaceuticals: Collaborator, Research support